Mengenal Sumber Daya Manusia (SDM): Pengertian Dan Fungsinya - Rubi Babullah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to get to know the basics of human resource management from an educational perspective. Human Resource Management (HR) in the educational context has an important role in ensuring the effectiveness and efficiency of the implementation of the education system. The main objective of HR management from an educational perspective is to achieve optimal educational quality through managing a quality workforce. The scope of educational HR management covers various aspects, from recruitment and selection to career development and performance evaluation. The Human Resources Department is a key element in the HR management process, responsible for the management, development and supervision of human resources in educational institutions. Therefore, a deep understanding of the concepts, functions, objectives and scope of HR management in the educational context is very important to improve the overall quality of education.